Clinical Readiness Program: Refocusing the Military Health System. (25th January 2021) - Holt, Danielle B; Hueman, Matthew T; Jaffin, Jonathan; Sanchez, Michael; Hamilton, Mark A; Mabry, Charles D; Bailey, Jeffrey A; Elster, Eric A
ABSTRACT: Introduction: The Military Health System serves to globally provide health services and trained medical forces. Military providers possess variable levels of deployment preparedness. The aim of the Clinical Readiness Program is to develop and assess the knowledge, skills, and abilities (KSAs) needed for combat casualty care. Methods: The Clinical Readiness Program developed a KSA metric for general and orthopedic surgery. The KSA methodology underwent a proof of concept in six medical treatment facilities. Results: The KSA metric feasibly quantifies the combat relevance of surgical practice. Orthopedic surgeons are more likely than general surgeons to meet the threshold. Medical treatment facilities do not provide enough demand for general surgery services to achieve readiness. Conclusion: The Clinical Readiness Program identifies imbalances between the health care delivery and readiness missions. To close the readiness gap, the Military Health System needs to recapture high KSA value procedures, expand access to care, and/or partner with civilian institutions.